Efficacy and safety of pneumatic trabeculoplasty versus timolol added to latanoprost in primary open angle glaucoma - Kocabora, Mehmet Selim; Özsütçü, Mustafa; Kandemir, Nilay; Göçmez, Erhan; Fazıl, Korhan; Gülkılık, Gökhan (Soc Editrice Univ, 2013)
Background. To compare the safety and short-term additive hypotensive effect of pneumatic trabeculoplasty (PNT) versus timolol among patients receiving topical latanoprost for primary open angle glaucoma (POAG). Patients and Methods. This study prospectively evaluated 30 eyes of 30 patients with POAG receiving latanoprost monotherapy. We randomly assigned 15 eyes to PNT plus latanoprost (Group A), and 15 eyes to latanoprost/ timolol fixed combination therapy (Group B). PNT treatment was performed at days 0, 7, and 90. Follow-up visits occurred at day 1, week 1, and months 1 and 3. Results. Compared to baseline values, both treatments significantly lowered IOP (p <= 0.001). The mean IOP for Group A was 21.13 +/- 1.6 mmHg at baseline and 18.7 +/- 1.5 mmHg at three months (p <= 0.001). For Group B, mean IOP was 20.8 +/- 1.9 mmHg at baseline and 18.9 +/- 0.8 mmHg at three months (p <= 0.001). Transient conjunctival hyperaemia, the only adverse effect occurring after PNT, was observed in all patients in Group A. Conclusion. The additive IOP-lowering effect of PNT was similar to timolol in patients with POAG receiving latanoprost.
WOS: 000325617700003
PubMed ID: 24045520
Keywords: Glaucoma; Intraocular Pressure; latanoprost; Pneumatic Trabeculoplasty; Timolol